Risky Decisions and the Opportunity Cost of Time - Jan Hausfeld; Sven Resnjanskij (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
We investigate the trade-off between the opportunity costs of decisions and their quality in a simple model. In a lab experiment, we introduce exogenous variation in the opportunity costs of time. Contrary to claims in the previous literature, we show that using more time when making small-stake decisions does not indicate irrational behavior, and neither does a positive correlation between decision time and the probability of making mistakes. Such behavior is compatible with rational decisionmaking and our causal experimental evidence and, hence, does not imply that people behave fundamentally irrational when making observable decision errors under risk.
Keywords: C91; D01; D81; D83; D91; 330; decision under risk; time constraints; opportunity costs; rational behavior; lab experiment; structural estimation; drift diffusion model